Design and modeling of a multiscale porous ceramic heat exchanger for high temperature applications with ultrahigh power density. (15th September 2022) - Li, Xiangyu; Wilson, Chad T.; Zhang, Lenan; Bhatia, Bikram; Zhao, Lin; Leroy, Arny; Brandt, Olivia; Orta-Guerra, Rodrigo; Youngblood, Jeffrey P.; Trice, Rodney W.; Wang, Evelyn N.
Highlights: Multiscale porous ceramic heat exchanger for high temperature applications. Hierarchical models to predict and optimize heat exchanger core. 2.8 × enhancement of the surface area to volume ratio compared to existing designs. Abstract: The efficiency of a heat engine can be significantly improved by operating in a high-temperature and high-pressure environment, which is crucial for a wide range of applications such as hybrid and electric aviation as well as power generation. However, such extreme operating conditions pose severe challenges to the heat exchanger design. Although recently developed superalloys and ceramics can survive high-temperature and high-pressure loads, using these materials in a traditional heat exchanger design requires high cost and yields low power density. In this work, we propose an ultrahigh power density ceramic heat exchanger for high-temperature applications enabled by a multiscale porous design. By optimizing the design of centimeter-scale macrochannels and microchannels, significant improvement to both heat transfer and structural strength is predicted, with a negligible pressure drop penalty (< 1%). Based on finite element simulations, an optimized heat exchanger core design is expected to achieve power densities of 717 MW/m 3 and 300 kW/kg, which indicates more than 2.5× enhancement in thermal performance compared to printed-circuit heat exchanger design. Furthermore, the heat exchanger design features low material costs and scalable fabrication, enabling highly customizable applications in aerospace and terrestrial power generation.